From microscale to mesoscale: The non-linear behavior prediction of 3D braided composites based on the SCA2 concurrent multiscale simulation. (8th September 2021) - He, Chunwang; Ge, Jingran; Gao, Jiaying; Liu, Jiapeng; Chen, Haosen; Liu, Wing Kam; Fang, Daining
Abstract: Compared with traditional phenomenological models, concurrent multiscale simulation is a powerful tool to capture the mechanical behavior of composites from different scales simultaneously. However, it is still a challenge to conduct a concurrent multiscale simulation for composites due to the huge computational costs. The aim of this paper is to solve the challenge by introducing an effective reduced order model (ROM), called the data-driven self-consistent clustering analysis (SCA). The SCA method solves the RVE problem into two stages. In the offline stage, the high-fidelity RVE of composites is compressed into a cluster-based RVE and the interaction tensor between two clusters is calculated. In the online stage, a cluster-based discrete incremental Lippmann-Schwinger equation is solved to get the local strain and stress responses. Based on SCA, a concurrent multiscale framework SCA 2 from microscale to mesoscale is proposed to capture the non-linear behavior of 3D braided composites. Firstly, the SCA-based results for yarn RVE and braided RVE are compared with the finite element (FE) results to verify the accuracy of the algorithm. Then, the SCA 2 framework is applied to simulate the uniaxial tension and compression of 3D braided composites, which is also validated with the experiments and shows great accuracy and high efficiency. The proposed SCA 2 framework will be extended into a three-scale concurrent simulation for the macroscopic structure analysis. Graphical abstract: Image 1